Vibration fault diagnosis and dynamic balance processing analysis of blower in thermal power plant. Issue 1 (March 2020) - Li, Peng; Pang, Le; Lin, Zhongpeng
Abstract: The fan vibration of the forced draft fan in a power plant is too large during normal operation, which seriously affects the normal operation of the unit. Through the vibration detection, on the basis of comprehensive analysis of the fan vibration failure mechanism, the means of adjusting the balance of the fan is adopted to reduce the excessive vibration to an excellent level. This paper introduces an excessive vibration fault caused by a device imbalance problem that is treated by vibration detection and dynamic balance test. The article elaborates the diagnosis method, diagnosis process and treatment suggestions, and deeply analyses and summarizes the characteristics of rotor imbalance, and provides reference for the diagnosis and analysis of the same type of fault.